Development and control of a robotic hand exoskeleton for assistance in self-feeding - Tay, Lip Ong (2015)
Stroke becomes one of the common diseases in the world. Many patients are suffering it and they have the disabilities of controlling hand motion. The main objective of project is to develop an assistive robotic hand design which helps the patients to conduct the rehabilitative exercises and even complete “activities of daily living” (ADLs) like eating and drinking. The literature review on robotic hand is conducted. There are many researches on robotic hand which can replace human hand or assist human hand to complete some motion tasks. Moreover, there are many mechanisms that can control the fingers by using motors. In this project, the cable-driven mechanism is selected as it meets the objectives of the project the most. Cable-driven mechanism can have a remote controlling platform to perform its control motion so that the exohand can have lighter weight and smaller size. Based on the design requirements, the morphological chart is built to interpret the function of the specific designs. From the morphological chart, three conceptual designs are developed by using Autodesk Inventor Software. One of the designs will be further developed in detailed after the design evaluation is done. On the other hand, the material selection and the control equipment are discussed in the project. Nevertheless, the prototype based on the improved design is fabricated and assembled with the mechanical parts such as screws, nuts and torsion springs bought from Misumi Company. Motion Manager Software is used to test the prototype with the control equipment. The assumption of frictionless motion is made in the theoretical analysis. Therefore, the project covers the result and discussion sections to analyze how it differs from the theory. Finally, the project concludes that the proposed exohand is feasible to meet the objectives of the project. The advices and suggestions on the future improvement are provided and discussed after the conclusion.